RELEVANSI PERDA NOMOR 3 TAHUN 1991 DALAM PEMBANGUNAN PARIW ISATA BUDAYA BALI - Hadi Sukarno, Teguh (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2007)
The Government of Bali decided that culture tourism concepts were viewed as the ideology, spirit, guidelines, framework and solutions in developing tourism in Bali. These decisions were then legitimized in a form of provincial rules